On beşinci yüzyıl şairi Sabayi ve Divançesi (transkripsyonlu metin-açıklamalar-dizin) - Kavaklık, Rüstem (My University, 2008)
Bu çalışma üç bölüme ayrılmıştır. Birinci bölümde, şairin hayatının ve edebí kişiliğinin incelenmesi yapıldı. Öncelikle şairle ilgili bilgi veren kaynaklarda yer alan bilgiler tasnif edildi ve şairin hayatının ana çizgileri belirlenmeye çalışıldı. Edebí kişiliği bölümünde dil ve üslûp özellikleri incelendi. İkinci bölümde transkripsiyonlu metne yer verildi. Metin şairin ele geçen şiirlerinden, Edirneli Nazmí ve Pervāne Beg nazire mecmualarından toplanan şiirlerle oluşturuldu. Yazmadaki kusurlar, şiirleri derleyenin yanlışları ve şairin üslûbundan kaynaklanan kimi aksaklıklar sebebiyle metinde anlaşılması güç yerler bulunmaktadır. Üçüncü bölüm, metnin dizininden oluşmaktadır. Kelimelerin metinde geçen hālleriyle dizinin verildiği bu bölümle, sonradan metin üzerinde yapılacak çalışmalara kolaylık sağlanmak istenmiştir.

This study is divided into three parts. The first chapter aims at uncovering the obscure periods in his life and his literary character. First of all, the data in the sources was classified and then his life was tried to be determined in main features. In the section giving his literary character some striking points in terms of language and style were touched. Second part covers the text. The text is composed of his available poems as well as from the ones taken from Edirneli Nazmi and Pervane Beg nazire mecmuas. For the couplets in the tezkires, they are added at the end of the text to the couplet part. Because of the deficiencies in the manuscript, the mistakes of the compiler and also the faults resulting from the style of the poet there are hard places to comprehend in the text. Third part consists of the index of the text. The section giving the words in their nominative cases aims at making the subsequent researches on the text easier.
Keywords: Türk Dili; Türk Dili_Şiir